Cognitive Phraseology in Spanish and Chinese: Conceptualization and Analysis of Some Somatisms - García Rodríguez, Joseph (2025)
In recent decades, the study of phraseology from a cognitive point of view has attracted great interest from researchers. Despite the published works, it is difficult to find exhaustive analyses that address the similarities and differences found between phraseological units of distant languages, such as Spanish and Chinese, whose analyses began at the beginning of the 21st century. Therefore, this research aims, on one hand, to extract the concepts underlying a bilingual corpus of 100 somatic idioms, specifically those formed with head, eye and hand, collected from various dictionaries, and on the other, to cognitively analyse these expressions with the purpose of contrasting their semantic properties and the metaphorical/metonymic mechanisms that form them. After the analysis, semantic properties and metaphorical and metonymic schemas shared by both languages are observed, although cultural differences are evident in the contrasted examples. The purpose of this study is to contribute to the development of a bilingual database that contains units belonging to different semantic fields to apply the results to other disciplines, such as Translation or Spanish as a Foreign Language.